A voz insidiosa da traição: tragédia, melodrama e fait divers em a mulher sem pecado, de Nelson Rodrigues - Sales, Ariela Fernandes (2014)
The current work intends to analyze betrayal in action at the play A mulher sem pecado, by Nelson Rodrigues. The perception that the title of genius author was compared to damned one, led us to observe which precepts led the author´s playwriting production, seeking the roots of his theater in Brazilian Modernism. Apart from the relations with such esthetic movement, we seek noticing, in his poetic, the importance of concepts connected to tragedy, to fait divers, and to melodrama, used at analysis, of chosen corpus. Talking about a handicapped husband´s obsession, Olegário, by his wife, Lídia, the play is about a constant persecution, with dynamic dialogues and tension measured by the interruption of such dialogues. Analysis allow us to say that Nelson Rodrigues endow the play of an occult complexity, weaving elements that hides, a conection of dramatic genre that leads on stage, trhough formal transgressions, the transgression of a woman which had no sins.